DESIGN of A SMALL PATCH ANTENNA at 3.5 GHZ for 5G APPLICATION - Ferdous N.; Chin Hock G.; Hamid H.A.S.; Raman M.N.A.; Sieh Kiong T.; Ismail M. (Institute of Physics Publishing, 2023)
Computer software; Energy conservation; Environmental technology; Microstrip antennas; Microwave antennas; Scattering parameters; Slot antennas; Antenna gains; Communication application; CST microwave studio; Epoxy material; Radiating patches; Resonating frequency; Small patch antennas; Substrate material; 5G mobile communication systems